Stelsels substitutie (reeks 1)

Hoofdmenu Eentje per keer 

Substitutie

  1. \(\left\{\begin{matrix}x+2y=11\\4x=6y-26\end{matrix}\right.\)
  2. \(\left\{\begin{matrix}-4x-2y=10\\x=-3y-10\end{matrix}\right.\)
  3. \(\left\{\begin{matrix}4y=32-4x\\-x-y=-8\end{matrix}\right.\)
  4. \(\left\{\begin{matrix}5x+6y=-43\\-2x+y=-10\end{matrix}\right.\)
  5. \(\left\{\begin{matrix}3y=2-2x\\3x-y=25\end{matrix}\right.\)
  6. \(\left\{\begin{matrix}2x-2y=-38\\-x-5y=-35\end{matrix}\right.\)
  7. \(\left\{\begin{matrix}-x+y=-18\\2x-6y=76\end{matrix}\right.\)
  8. \(\left\{\begin{matrix}2x+5y=14\\-x=-2y+11\end{matrix}\right.\)
  9. \(\left\{\begin{matrix}5x-3y=44\\-x=6y-22\end{matrix}\right.\)
  10. \(\left\{\begin{matrix}3x-2y=17\\2x+y=-12\end{matrix}\right.\)
  11. \(\left\{\begin{matrix}-5x-6y=-26\\6x=-y+56\end{matrix}\right.\)
  12. \(\left\{\begin{matrix}-3y=12+x\\5x-2y=-43\end{matrix}\right.\)

Substitutie

Verbetersleutel

  1. \(\left\{\begin{matrix}x+2y=11\\4x=6y-26\end{matrix}\right.\qquad V=\{(1,5)\}\)
  2. \(\left\{\begin{matrix}-4x-2y=10\\x=-3y-10\end{matrix}\right.\qquad V=\{(-1,-3)\}\)
  3. \(\left\{\begin{matrix}4y=32-4x\\-x-y=-8\end{matrix}\right.\qquad V=\{(6,2)\}\)
  4. \(\left\{\begin{matrix}5x+6y=-43\\-2x+y=-10\end{matrix}\right.\qquad V=\{(1,-8)\}\)
  5. \(\left\{\begin{matrix}3y=2-2x\\3x-y=25\end{matrix}\right.\qquad V=\{(7,-4)\}\)
  6. \(\left\{\begin{matrix}2x-2y=-38\\-x-5y=-35\end{matrix}\right.\qquad V=\{(-10,9)\}\)
  7. \(\left\{\begin{matrix}-x+y=-18\\2x-6y=76\end{matrix}\right.\qquad V=\{(8,-10)\}\)
  8. \(\left\{\begin{matrix}2x+5y=14\\-x=-2y+11\end{matrix}\right.\qquad V=\{(-3,4)\}\)
  9. \(\left\{\begin{matrix}5x-3y=44\\-x=6y-22\end{matrix}\right.\qquad V=\{(10,2)\}\)
  10. \(\left\{\begin{matrix}3x-2y=17\\2x+y=-12\end{matrix}\right.\qquad V=\{(-1,-10)\}\)
  11. \(\left\{\begin{matrix}-5x-6y=-26\\6x=-y+56\end{matrix}\right.\qquad V=\{(10,-4)\}\)
  12. \(\left\{\begin{matrix}-3y=12+x\\5x-2y=-43\end{matrix}\right.\qquad V=\{(-9,-1)\}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-06-27 06:54:06